Development Strategy of Cokelat Makaryo MSME in Kulon Progo Based on SWOT and QSPM Approach - Nurhidayah, Khusnita; Suprihanti, Antik (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2026)
Cokelat Makaryo is MSME that producing palm sugar chocolate with several certifications. However, the business faces problems related to underdeveloped digital marketing, fluctuating revenue, suboptimal research and development (R&D) and unstable prices of key raw materials due to the absence of partnerships with cocoa farmers. This study aimed to (1) identify the internal and external environmental conditions for business development, (2) analyze alternative strategies, and (3) determine priority strategies for the development of Cokelat Makaryo MSME. The research employs a quantitative descriptive method with a case study approach, utilizing IFE, EFE, IE matrices, SWOT, and QSPM analysis. The results of this study showed (1) The primary strength of Cokelat Makaryo MSME was holding certifications, including the Halal, NIB, PIRT, and Jogjamark labels. The main weakness identified was the absence of price agreements with supplier farmers, resulting in fluctuating raw material prices. The principal opportunity was the institutional support provided by the Cooperative Office in facilitating product promotion at Yogyakarta International Airport (YIA). The main threat was the competition from similar enterprises that are more established and more widely recognized. (2) There were three alternative strategies: offering an educational chocolate processing service through an open kitchen concept, strengthening product branding through customization and certification targeting premium markets and spesial occasions, and enhancing digital marketing and penetrating the national market. (3) The priority strategy for business development is to strengthening product branding through customization and certification targeting premium markets and spesial occasions.